Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n206
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical pre-treatment for separation of bio-waste from municipal solid waste: case study of district in Latvia

Abstract: The mechanical pre-treatment technologies are one of the solutions that are planned to be used in all waste management regions to separate biodegradable municipal waste in Latvia, thus inter alia contributing to implementation of the waste policy of the European Union. In Latvia recent research of the collected household waste composition shows that average bio-waste is 39 %. The article provides the results of experimental work for partly sorted municipal solid waste mechanical pre-treatment in Latvia. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This is explained by the fact that even before shredding the waste already had an inherent component of smaller particle sizes. Presence of such small particles in MSW was previously reported in literature [56,57].…”
Section: Further Observations From the 'Dry' Mechanical Treatments Using Shredding Equipment (Trials 1 To 12c)supporting
confidence: 62%
See 1 more Smart Citation
“…This is explained by the fact that even before shredding the waste already had an inherent component of smaller particle sizes. Presence of such small particles in MSW was previously reported in literature [56,57].…”
Section: Further Observations From the 'Dry' Mechanical Treatments Using Shredding Equipment (Trials 1 To 12c)supporting
confidence: 62%
“…This supports the earlier observation that MSW contains a substantial inherent fraction of small-size particles (usually around 5% and up to 10% w/w of <5 mm in the earlier trials of this study) and suggests that this fraction incorporates a significant amount of inert material. It has previously been reported that the fine fraction of MSW contains elevated proportions of inert materials such as sand [56]. The presence of sand and similar inert materials is unfavourable in bioprocessing, since it causes abrasion of technical equipment, reduced operating reactor volume as result of accumulating inert fractions (in particular in wet anaerobic digestion) and a need for regular removal of such material from the reactor [58].…”
Section: Wet Processing Of Test Materials With the Macerating Grindermentioning
confidence: 99%